Regiopoetyka? Wstępne uwagi na temat nowego projektu - Mikołajczak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The aim of this article is to outline the regiopoetics project seen as a new scientific discipline within regional literature studies initiated by Stefania Skwarczyńska. Regiopoetics involves traditional such poetics issues as genology, language, fictional character, reception, etc., all of which, with regional factor and profiled from the contemporary cultural researches, belonging to the field of new regionalism in literary studies. These categories are not of descriptive nature only – they are modern operational tools in the study of important issues of the present day with regard to region. The article also presents reflections on the status of regional research in literature science with reference to Skwarczyńska’s research concept and her outline of possible shared sphere in literary studies and region.